2021
DOI: 10.1101/2021.06.04.447039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-transfecting GMO-PMO and PMO-GMO chimeras enable gene silencingin vitro and in vivozebrafish model and NANOG Inhibition Induce the Apoptosis in Breast and Prostate Cancer Cells

Abstract: Phosphorodiamidate Morpholino Oligonucleotides (PMOs)-based antisense reagents cannot enter inside cells by itself without the help of any delivery technique which is the last hurdle for their clinical applications. To overcome this limitation, a self-transfecting GMO-PMO or PMO-GMO chimeras has been explored as a gene silencing reagent where GMO stands for guanidinium morpholino oligonucleotides which linked either at the OH- or NH-end of PMOs. GMO not only facilitates cellular internalization of such chimera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Recently, two PMO-based drugs, Eteplisren (Exondys 51) and Golodirsen (Vyondis 53 TM ), were approved by FDS for the treatment of Duchenne muscular dystrophy (DMD), owing to their safety and efficacy [ 142 , 143 ]. Later in 2021, Jayanta et al reported that cell-penetrating PMO induced translational repression of genes involved in prostate and breast cancer [ 144 ].…”
Section: Mirna Therapeuticsmentioning
confidence: 99%
“…Recently, two PMO-based drugs, Eteplisren (Exondys 51) and Golodirsen (Vyondis 53 TM ), were approved by FDS for the treatment of Duchenne muscular dystrophy (DMD), owing to their safety and efficacy [ 142 , 143 ]. Later in 2021, Jayanta et al reported that cell-penetrating PMO induced translational repression of genes involved in prostate and breast cancer [ 144 ].…”
Section: Mirna Therapeuticsmentioning
confidence: 99%
“…Researchers also need to explore other potential gene silencing agents apart from non-coding RNAs to achieve targeted gene silencing like GMO-PMO or PMO-GMO chimeras as designed by Professor Sinha and co-workers. [14] Toxicity profile and efficacy of RNAi therapeutics in humans cannot be predicted from in-vitro systems or even from in-vivo murine model due to yet to be determined reasons. [23] It is also not feasible to test the large number of delivery vehicles, which are being developed in non-human primate models.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13] Recently, Professor Surajit Sinha and his group have developed a GMO-PMO or PMO-GMO chimeras (International Publication Number -WO 2011/018798 A2) (Figure 2c) which are soluble in culture media and can penetrate cells without the need of injection. [14] GMO is guanidinium morpholino oligonucleotides which are linked either at the OH-or NHend of the PMOs.…”
Section: Introductionmentioning
confidence: 99%
“…PMOs must be chemically modified to improve cellular uptake and pharmacokinetics. , Among the reported modifications, incorporation of a guanidinium linkage or guanidinium-functionalized nucleobase is notable . Sinha’s group demonstrated the cell-penetrating and gene-silencing properties of self-transfecting guanidinium morpholino–PMO chimeras in cell culture and zebrafish .…”
mentioning
confidence: 99%